PENGARUH PROFESIONALISME PEMERIKSA PAJAK, PENGALAMAN KERJA, TINGKAT PENDIDIKAN, DAN MOTIVASI KERJA TERHADAP KINERJA PEMERIKSA PAJAK (Studi pada Pemeriksa Pajak di Kanwil DJP Jakarta Pusat) - Aditya, Ritonga Nugraha; Vince, Ratnawati; Eka, Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research objective was examined the influence of tax auditor Profesionalism, work experience, the level of education, and work motivation on thePerformance Tax Inspector (Studi Of Tax Inspectors In Kanwil DJP JakartaPusat) The data in this study is the primary data. The population this study werethe tax auditors who worked at Kanwil DJP Jakarta Pusat. The sampling methodused in this study census method. The sample usedin this study were 34respondent. The method of data analysis used to the test the hypotesis is multipleregression analysis using SPSS version 21. The results of this study tax auditorProfesionalism, work experience, the level of education, and work motivationshowed influence on the tax auditor performance. The magnitude of the effectcaused by Adjusted R² by three variables is 73% of the dependent variable, whilethe remaining 27% is influenced by other independent variable that are notobserved in this study.Keywords : Profesionalism, tax auditor, work experience, the level of education,work motivation, performance